PEMANFAATAN LIMBAH FLY ASH DARI PEMBAKARAN BATUBARA PADA PEMBUATAN SEMEN PCC (PORTLAND COMPOSITE CEMENT) DI PT SEMEN XYZ LAMPUNG - Dwi Sari; Susanti Sundari (Fakultas Teknik Universitas Tulang Bawang Lampung, 2020)
This study discusses the use of fly ash waste from coal burning on the manufacture of PCC (Portland composite cement) at PT. XYZ Lampung. The purpose of this research is to look at the technical studies and the efficiency of raw materials in the use of fly ash in cement making, in this case PCC cement (Portland Composite Cement). The steps taken in analyzing the data in this study were viewed from a technical aspect by means of a physical test, namely the cement compressive strength test at the age of 3 days, 7 days, and 28 days using the Compression Testing Machine. This test was conducted to see the comparison of the compressive strength of PCC cement using limestone and fly ash as raw materials, then calculate the difference in raw material costs in the year before and after the replacement of limestone with fly ash. The results showed that cement with the addition of fly ash after 3 days, 7 days and 28 days had an increased compressive strength value, which increased 21.69%, 16.07% and 8.05% respectively of the compressive strength of cement using limestone. The use of fly ash as a substitute for limestone has an effect on the cost of raw materials, where the difference between the cost of raw materials in 2019 and the cost of raw materials in 2018 is Rp. 39,440,952,074.